2021
DOI: 10.21203/rs.3.rs-29955/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of nutrition knowledge, practice, supplement use and nutrient intake with athletic performance among Taekwondo players in Nepal

Abstract: Introduction: Adequate knowledge on nutrition and dietary intake are important to enhance the athletic performance. When athletes’ nutrition requirements are not met, they are more likely to be exhausted compromising athletic performance. The main objective of this study was to measure the association of nutritional knowledge, practice, supplement use, and nutrient intake with athletic performance among Nepalese Taekwondo (TKD) players. Methodology: We conducted an analytical cross-sectional study among 293 Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(60 reference statements)
1
0
0
Order By: Relevance
“…In another study, 56.3% of the competitive athletes had poor nutritional knowledge-NK, and 55.6% of them had poor nutrition practice-NP scores. At the same time, it was found that 7.2% of the participants used ergogenic nutritional aids and preferred protein powder mostly (Sunuwar et al, 2021). In the current study, low scores on the sports nutrition knowledge questionnaire, which were answered by the individuals who used ergogenic aids, showed that the athletes use ergogenic supplements haphazardly (Table 4).…”
Section: Discussionsupporting
confidence: 47%
“…In another study, 56.3% of the competitive athletes had poor nutritional knowledge-NK, and 55.6% of them had poor nutrition practice-NP scores. At the same time, it was found that 7.2% of the participants used ergogenic nutritional aids and preferred protein powder mostly (Sunuwar et al, 2021). In the current study, low scores on the sports nutrition knowledge questionnaire, which were answered by the individuals who used ergogenic aids, showed that the athletes use ergogenic supplements haphazardly (Table 4).…”
Section: Discussionsupporting
confidence: 47%